Linguagem e esquizofrenia: de coisas e palavras - Miguelez, Oscar Manuel (2011)
This thesis addresses the issue of language in schizophrenia. First, schizophrenia is defined, as a nosographic category, derived from its predecessor dementia praecox , conceived by Bleuler as a psychopathological concept. This is followed by a discussion on some developments of this concept in the context of psychiatry. The thesis finally focuses on Freudian hypotheses about schizophrenia, which have emerged in a moment of rapprochement between psychoanalysis and psychiatry. An emphasis is given on the relationship between words and things in the metapsychological texts. The foundation of the Freudian word / thing relation, initially linked to Stuart Mill s theory of names, is examined, as are other ways of thinking this relation, as well as schizophrenia symptoms, by Lacan, Foucault, Agamben and contemporary French psychoanalysis authors. These and other issues were addressed by presenting three clinical cases: Wolfson, Mané and Edgar. These cases illustrate the diversity of language disorders in schizophrenia, ranging from deconstruction / reconstruction of the entire language (Wolfson) to the occasional presence of a few strange words, keys for the delusional construction (Mané and Edgar). Despite the differences, these cases share a similar rupture. The central hypothesis of this thesis is that such rupture, unlike what has previously been postulated by Freud, is not a break in the word / thing relation, but on the intersubjective function of language, the ability to use language as a way to bond to each other. This rupture is followed by the search for procedures and all sorts of attempts to recovering the lost connection. In this sense, the two times of psychosis, proposed by Freud, have proved fruitful